Kurikulum 2013 Mata Pelajaran Bahasa Arab Kelas 8 Di Madrasah Stanawiyah (Implementasi, Analisis Dan Pengembangannya) - Imam Hasani; Eva Siti Faridah (IHSANIKA : Jurnal Pendidikan Agama Islam, 2024)
The 2013 curriculum is a tool that can determine the direction and goals of education, therefore, the implementation and development of the curriculum is very important to carry out. The aim of this research is to describe the implementation and development of the 2013 curriculum in Arabic language learning in class VIII at MTS. The method used in this research is content analysis, with a descriptive qualitative research type. Based on the research results, it is very important to optimize the implementation of the 2013 Curriculum in Arabic language subjects at Madrasah Tsanawiyah, so that the quality of Arabic language learning can increase and can provide enjoyable learning and can measure the achievement of the three aspects (attitudes, knowledge and skills) which are used as assessments. in the 2013 curriculum. Then the implementation of the Arabic language curriculum can run optimally if it is supported by commitment from teaching staff or teachers, school principals, guidance from related parties and supported by adequate facilities, especially in the field of technology.